Effects of gelam honey and fluorouracil (5-FU) against human colorectal cancer HT-29 cells - Abd Manaf, Ali; Syed Ahmad Tajudin, Tuan Johari; Fatimah, Hashim; Wan Iryani, Wan Ismail (2017)
Gelam or Melaleuca Honey (GH) is the honey of Apis mellifera from the forest of Melalueca spp in Malaysia widely being studied, but combinatorial effects with drugs is still lacking. Thus, this study was carried out to determine combinatorial effects of Gelam honey and 5-FU on human colorectal cancer HT-29 cells. In this study, MTT assay was done to determine the cytotoxic dose. Cells membrane changes was observed in AO/PI assay. Early event of apoptosis detection were done by annexin-v FITC and mitochondria membrane potential. TUNEL assay was performed to examine the fragmented DNA.The results for MTT assay showed that the IC50 for gelam honey and 5-FU alone were 36.2 mg/ml and 15.5 µg/ml. Meanwhile, the IC50 of combination treatment was 13.2 mg/ml for gelam honey, respectively. The combination index was < 1 suggesting the synergism.Early event of apoptosis was occurred in all treatment groups but with different percentage. Combinatorial treatment in apoptosis detection assay showed the highest percentage among other treatment groups. In conclusion, combinatorial treatment of gelam honey and 5-FU may be an effective's chemotherapy strategy in fighting colon cancer cells.